Implementation of Philosophy of Religion Principles In Islamic Education of Islamic Boarding School - Encung, Encung; Rusydi, Ibnu (Tafkir: Interdisciplinary Journal of Islamic Education, 2026)
This study analyzes the implementation of Theo-Humanism concept of God-centered to build humanized-God centered character in Islamic boarding school education of Tahfidz Al-Amien Prenduan, Sumenep, Madura. Applicating qualitative instrumental case study design involving 16 key respondents, consisting of students, teachers, and institutional stakeholders, selected through purposive sampling. The research explored field data through in-depth interviews with the key respondents, applying triangulation across time and methods to ensure data credibility. In addition, participatory observation was conducted throughout educational and instructional activities, with a primary focus on examining teacher–student relationships, analyzing curricular documents, and eliciting students’ experiential narratives. The findings indicate that the integration of Divine and human values is manifested in an integrated curriculum model that harmonizes naqli (revealed) and aqli (rational) forms of knowledge. This integration is grounded in a collaborative educational system implemented on a 24-hour basis under the close supervision of educators who function as murabbi, mudabbir, and khādim al-tarbiyah. Such an approach strengthens ethical and moral education based on Theo-Humanist principles, which serve as the fundamental foundation for shaping students’ character oriented toward their role as al-khalīfah fī al-arḍ (God’s vicegerents on earth) representing the highest recognition of human dignity in fulfilling life in the world.